Case Report: 18F-PSMA PET/CT May Improve the Clinical Management of Penile Metastases From Prostate Cancer - Fan, Junjie; Liang, Hua; Zhang, Xing; Chen, Xingfa; Duan, Xiaoyi; Li, Lei; He, Dalin; Wu, Kaijie (Frontiers in Oncology, 2021)
Metastases from prostate cancer (PCa) to the penis are extremely rare, and few case reports exist in the literature. Because most patients usually present with multiple distant metastases at diagnosis, the prognosis is very poor. With the wide application of prostate-specific membrane antigen (PSMA) PET/CT, penile metastases may be detected at an early stage. Thus, questions regarding whether early diagnosis and precise treatment will equate to a survival advantage have recently been raised. In the present study, we reported 3 cases of penile metastasis from castration-resistant PCa. Moreover, a patient with asymptomatic penile metastases was diagnosed by 18F-PSMA PET/CT followed by lesion biopsy, and the prognosis was very well, despite with an aggressive pathological feature and low treatment intensity. In addition, we performed a literature review and found 62.5% of asymptomatic penile metastases were diagnosed by PSMA PET/CT in past seven years. Thus, we believe that PSMA PET/CT may detect more asymptomatic penile metastases in future, which led to early diagnosis, treatment and survival advantage.